Molecular Biological Significance of Cell Cycle Proteins in Colon Cancer Bargained by Gene Mutations And DNA/RNA Viruses. - Kuzniatsou, Aleh E.; Tsyrkunov, Vladimir; deeb Hussein Ali, Ali (Journal of Biomedicine and Biochemistry, 2024)
Genetic mutations in BRCA1/2 and hMSH2 genes, as well as viral infections, have been implicated in colon cancer (CC) development and progression.Aim: To evaluate the molecular characteristics of cell cycle proteins (p53,bcl-2, NF1, pRb1) in colon cancer cases burdened by gene mutations (BRCA1/2, hMSH2) and DNA/RNA viruses.Methods: A molecular biological and immunological study was performed: cycle proteins NF1, p53, bcl-2, pRb1, viruses (HSV1/2, HHV6, CMV, VEB, HCV, HBV, HVP), BRCA 1/2 genes, hMSH2 gene.Results: The number of mutations in the BRCA1/2, and hMSH2 genes in blood samples from individuals with CC was 2.04%, while the frequency of changes in the hMSH2 gene was 4.17%, which is lower than the frequency of mutations in the same genes in tumor tissue samples – 7.98% (p=0.003). The occurrence of BRCA1/2 gene mutations among women showed their dependence on CC with exons of the hMSH2 gene. Viruses isolated in tumor tissue: HSV 1/2 – 86.8%, HHV6 – 25.0%, CMV – 10.3%, HCV 4.4%, HBV – 2.94%, HVP – 4, 1%, VEB – 19.1%, mixed inertia – 11.76%. Proteins p53, bcl-2, pRb1, and NF1 in intestinal tissue did not depend on the age and gender of patients.Conclusion: This study provides compelling evidence for the role of cell cycle proteins as diagnostic markers in colon cancer. The levels of p53, bcl 2, pRb1, and NF1 were significantly elevated in the Blood and tumor tissue of colon cancer patients compared to healthy controls.